2006
DOI: 10.1097/01.blo.0000203489.21206.a9
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of Posterior Malleolar Fractures Provides Greater Syndesmotic Stability

Abstract: Syndesmotic injuries are common in ankle fractures. Traditional syndesmosis fixation may be associated with a secondary procedure. When the posterior malleolus is fractured, the posterior syndesmotic ligaments may remain intact and attached to the fragment. Our goals were to establish the incidence of syndesmotic ligament ruptures in pronation-external rotation type ankle injuries associated with posterior malleolar fractures, and to assess syndesmotic stability after fixation of the posterior malleolus compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
210
1
11

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(243 citation statements)
references
References 47 publications
6
210
1
11
Order By: Relevance
“…If there is still instability in the presence of a Volkmann triangle, the fragment must be fixed. Fixing the Volkmann triangle is a better option than fixing the ankle mortise with a positioning screw [25].…”
Section: Resultsmentioning
confidence: 99%
“…If there is still instability in the presence of a Volkmann triangle, the fragment must be fixed. Fixing the Volkmann triangle is a better option than fixing the ankle mortise with a positioning screw [25].…”
Section: Resultsmentioning
confidence: 99%
“…Our biomechanical study suggested fixation of the posterior malleolus fracture restores more stability to the syndesmosis than transsyndesmotic fixation alone [10]. Studies using preoperative MRI to evaluate ankle fractures suggest fracture patterns that include an associated posterior malleolar fracture reliably have an intact posteroinferior tibiofibular ligament (PITFL) [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Nonetheless, fragments bigger than 25-30% of the articular surface and with articular incongruence (anteroposterior difference greater than 2 mm), the internal fixation of the fragment is indicated. 6,22,23 In this sense, a posterolateral approach provides a more direct access due to space created between the fibular and Achilles tendons. 6 In addition, bilateral weight-bearing at early stages of rehabilitation may enhance the outcomes of the internal fixation.…”
Section: Discussionmentioning
confidence: 99%